Oxidase‐Like Fe‐N‐C Single‐Atom Nanozymes for the Detection of Acetylcholinesterase Activity. Issue 43 (4th September 2019) - Wu, Yu; Jiao, Lei; Luo, Xin; Xu, Weiqing; Wei, Xiaoqian; Wang, Hengjia; Yan, Hongye; Gu, Wenling; Xu, Bo Z.; Du, Dan; Lin, Yuehe; Zhu, Chengzhou
Abstract: Single‐atom catalysts (SACs) have attracted extensive attention in the catalysis field because of their remarkable catalytic activity, gratifying stability, excellent selectivity, and 100% atom utilization. With atomically dispersed metal active sites, Fe‐N‐C SACs can mimic oxidase by activating O2 into reactive oxygen species, O2 − radicals. Taking advantages of this property, single‐atom nanozymes (SAzymes) can become a great impetus to develop novel biosensors. Herein, the performance of Fe‐N‐C SACs as oxidase‐like nanozymes is explored. Besides, the Fe‐N‐C SAzymes are applied in biosensor areas to evaluate the activity of acetylcholinesterase based on the inhibition toward nanozyme activity by thiols. Moreover, this SAzymes‐based biosensor is further used for monitoring the amounts of organophosphorus compounds. Abstract : Fe‐N‐C single‐atom nanozymes with distributed FeN2 active sites possessing oxidase‐like activity are reported. Based on the inhibition mode by thiols, the Fe‐N‐C single‐atom nanozymes show promising application for evaluating the activity of acetylcholinesterase and constructing sensitive biosensors to detect mercapto molecules and organophosphorus compounds.